Older people, the natural environment and common mental disorders: cross-sectional results from the Cognitive Function and Ageing Study - Wu, Yu-Tzu (BMJ Open, 2015)
OBJECTIVES: To explore the hypothesis that higher exposure to natural environments in local areas is associated with a lower odds of depression and anxiety in later life. DESIGN: A cross-sectional study based on the year-10 interview of the Medical Research Council Cognitive Function and Ageing Study (CFAS), a population-based study of ageing in the UK. Postcodes of the CFAS participants were mapped onto small geographic units, lower-layer super output areas (LSOAs) and linked to environmental data from government databases. The natural environment was characterised as the percentage of green space and private gardens in each LSOA based on the UK Generalised Land Use 2001 Dataset. PARTICIPANTS: 2424 people aged 74 and over in the CFAS year-10 follow-up interview (2001) from 4 English centres (Cambridgeshire, Nottingham, Newcastle and Oxford). MAIN OUTCOME MEASURES: Depression and anxiety; clinical and subthreshold cases were identified using the Geriatric Mental State Examination (GMS) package and its associated diagnostic algorithm: the Automated Geriatric Examination for Computer Assisted Taxonomy. RESULTS: Compared with the lowest quartile, living in the highest quartile of neighbourhood natural environment provision was associated with a reduced odds of subthreshold depression (OR 0.66, 95% CI 0.46 to 0.95), anxiety symptoms (OR 0.62, 95% CI 0.46 to 0.83) and their co-occurrence (OR 0.55, 95% CI 0.35 to 0.84) after adjusting for individual-level factors. Controlling for area deprivation attenuated the strength of associations for subthreshold depression by 20% but not for anxiety symptoms or for co-occurrence of the conditions. CONCLUSIONS: A high exposure to natural environments (green space and gardens) in communities was associated with fewer mental disorders among older people. Increasing provision of green environments in local areas could be a potential population-level intervention to improve mental health among older people.